The Effect Of Transfer Pricing, Foreign Ownership, And Capital Intensity On Tax Avoidance - Bulan Eprila Eprila; Septi Wulandari Chairini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research is crucial due to the need to understand the influence of capital intensity, foreign ownership, and transfer pricing on tax evasion practices in non-cyclical consumer sector companies listed on the IDX during the 2021–2023 period. Given the substantial contribution of this sector to the economy, evaluating how these companies manage their tax responsibilities is highly relevant. The study employs a quantitative approach using panel data regression, alongside estimation techniques such as the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). To ensure the model's accuracy, the coefficient of determination test is applied. The findings reveal that transfer pricing has a significant impact on tax evasion, while foreign ownership and capital intensity do not show a notable influence. However, when considered simultaneously, all three variables affect tax evasion. These results provide valuable insights for policymakers aiming to mitigate tax evasion practices and offer an empirical contribution to the existing taxation literature.